1997
DOI: 10.1597/1545-1569_1997_034_0226_swfaas_2.3.co_2
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with Facial Appearance among Subjects Affected by a Cleft

Abstract: Objective This study examined the satisfaction of patients with clefting and their parents with facial appearance and how this alters with age. The relationship between satisfaction with appearance and psychosocial functioning was also examined. Design Prospective Setting Subjects were recruited for the study from nine hospital-based clinics. Patients, Participants All subjects had some type of cleft and were 10, 15, or 20 years of age. In all, 111 subjects with clefting and 62 parents were included. Main Outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 10 publications
3
57
0
1
Order By: Relevance
“…The presence of a visible scar resulted in greater unhappiness with facial appearance. This is similar to the findings of Broder et al (1994) and Thomas et al (1997), who reported that subjects with visible defects expressed greater dissatisfaction with their appearance than subjects with nonvisible defects did. Furthermore, when the current data were examined using multiple regression analysis, having a visible scar was a strong predictor of unhappiness with facial appearance.…”
Section: Discussionsupporting
confidence: 89%
“…The presence of a visible scar resulted in greater unhappiness with facial appearance. This is similar to the findings of Broder et al (1994) and Thomas et al (1997), who reported that subjects with visible defects expressed greater dissatisfaction with their appearance than subjects with nonvisible defects did. Furthermore, when the current data were examined using multiple regression analysis, having a visible scar was a strong predictor of unhappiness with facial appearance.…”
Section: Discussionsupporting
confidence: 89%
“…Children with orofacial clefts also have a higher risk of developmental problems, including cognitive performance (Jocelyn et al, 1996;Jelliffe-Pawlowski et al, 2003). Treatment of orofacial clefts extends throughout adolescence, during which psychological adjustment has been reported to be a problem as well (Kapp-Simon et al, 1992;Thomas et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The announcement of a facial malformation affecting their child is a major psychological test for parents. Other studies [10,[31][32][33] have found that parents' first relationships with their children are based on conscious and unconscious emotions, which essentially involve touch, sound of voice, gaze, and facial expression.…”
Section: Parent's Relationship and Quality Of Lifementioning
confidence: 99%